Employment Recovery Stalls in Europe and Central Asia - Koettl, Johannes; Mata, Elizabeth; Saiovici, Gady; Santos, Indhira (World Bank, Washington, DC, 2014)
Employment recovery stalls in Europe and Central Asia (ECA) and Gross Domestic Product (GDP) continues to recover in most ECA countries, but the recovery remains fragile. Growth prospects remain poor in a number of countries where GDP continues to decline. This slowdown in the economic recovery is also evident at the sub-regional level. Unemployment has stabilized, with an average unemployment rate of 12 percent across the ECA region. Since the start of the crisis, men have been disproportionally hit by unemployment. The recent pace of job creation has not been sufficient to absorb the large pool of unemployed, resulting in growing long-term unemployment. Despite the rise in long-term unemployment, activity rates have increased or remained constant in most countries since 2008. ECA labor markets adjusted to the crisis not only through higher unemployment, but also through fewer work hours. Given the already low levels of employment in the region and a bleak demographic outlook, avoiding labor market detachment among the long-term unemployed, the inactive, and youth is the main challenge for policy makers in the near term.